Digital labour platforms and national employment policies in China: Studying the case of food delivery platforms - Yujie Chen; Ping Sun (International Labour Organization (ILO), 2023)
The paper analyses in general the impact of digital labour platforms on employment in China, the key challenges and how digital labour platforms has contributed to job creation. It discusses in-depth the case of food delivery platforms and presents the findings about the impact of food-delivery sector on employment. By reviewing the national employment policies in China over the two decades, the paper shares the experience on how the national employment policy frameworks have evolved in response to different employment challenges. New challenges posed by digital labour platforms for the national employment policies are identified and based on the comparison with recent employment policies at national and provincial levels, the paper concludes with suggestions on how to promote decent employment in the platform economy by making employment policies beyond the traditional frameworks.
Keywords: 330; Digitale Plattform; Logistikdienstleister; Gastronomie; Beschäftigungseffekt; Arbeitsmarktpolitik; China